Islamic Digital Parental Mediation and Children’s Willingness to Learn Religion: A Contemporary Islamic Psychology Perspective - Saimun Saimun; Hanafi Hanafi (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The development of digital technology presents both challenges and opportunities in children's religious education, particularly regarding the role of parents as mediators of Islamic values. This study aims to analyse the role of parents' Islamic digital mediation in shaping children's willingness to learn about religion and to contribute conceptually to the development of adaptive Islamic parenting patterns in the digital age. The method used is a Systematic Literature Review (SLR) that examines 30 peer-reviewed articles published between 2015 and 2025, obtained from Google Scholar, Scopus, and DOAJ. The analysis was conducted through systematic synthesis to integrate findings on digital mediation, the psychological mechanisms underlying Muslim children's development, and factors that support and hinder religious learning. The results of the study indicate that restrictive, active, and co-viewing mediation patterns that align with the values of tarbiyah, ta'dib, and uswah hasanah play a significant role in increasing children's motivation, understanding of worship, character, and religious identity. The implication is that Islamic digital parenting should be positioned as an educational and preventive strategy to support children's psychological and spiritual development in the digital age.